Edges of Layered FePSe3 Exhibit Increased Electrochemical and Electrocatalytic Activity Compared to Basal Planes - Wert, Stefan; Iffelsberger, Christian; K Padinjareveetil, Akshay Kumar; Pumera, Martin (ACS applied electronic materials, 2023)
Transition metal trichalcogenphosphites (MPX3), belonging to the class of 2D materials, are potentially viable electrocatalysts for the hydrogen evolution reaction (HER). Many 2D and layered materials exhibit different magnitudes of electrochemical and electrocatalytic activity at their edge and basal sites. To find out whether edges or basal planes are the primary sites for catalytic processes at these compounds, we studied the local electrochemical and electrocatalytic activity of FePSe3, an MPX3 representative that was previously found to be catalytically active. Using scanning electrochemical microscopy, we discovered that electrochemical processes and the HER are occurring at an increased rate at edge-like defects of FePSe3 crystals. We correlate our observations using optical microscopy, confocal laser scanning microscopy, scanning electron microscopy, and electron-dispersive X-ray spectroscopy. These findings have profound implications for the application of these materials for electrochemistry as well as for understanding general rules governing the electrochemical performance of layered compounds.